Combined Laryngocele Appeared Typical Findings - Eyibilen, Ahmet; Karagöz, Saliha; Yıldırım, Nezahat (Fırat University, 2007)
Laryngocele is an air filled dilatation of laryngeal saccule. The etiology is extractly unknown. Laryngocele is described as laryngomucocele distended with mucus produced by mucous gland near the aperture of the saccule. Here, we report a combined laryngocele showed air-fluid level in the cavity ©2007, Firat University, Medical Faculty

Larengosel larenks sakkülünün havayla dolu bir şekilde genişlemesidir. Nedeni tam olarak bilinmemektedir. Sakkül lümeni yakınında mukus salgılayan bezlerin salgılarıyla içi mukusla dolduğunda larengomukosel adını alır. Bu yazıda, kese içinde hava-sıvı seviyesi olan ve içinde bir miktar mukus bulunan mikst tipte bir larengosel olgusu sunulmuştur. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Tipik Bulgular Gösteren Mikst Larengosel